Nurses’ Family Support System in Pandemic Covid-19 - Rizqi Wahyu Hidayati; Novita Nirmalasari; Ike Wuri Winahyu Sari (Poltekkes Kemenkes Semarang, 2022)
Background: The Covid-19 pandemic is being 2 years and the fluctuated cases made the nurses workload were increasing. The effects are stress, anxiety, and burnout. To decrease these sequences, need family support. Family support advantage to them for increasing their confidence and being valuable. Purpose: the major aim of the study is to know the difference between family support for nurses who work in Covid and non-Covid wards.Methods: Quantitative method were used in its study and used 149 nurses as a respondent. The inclusion criteria were working at hospital at least a year and lived with nuclear family. The questioner used Family Support Scale (FSS) with 19 sentences. It used Mann-Whitney test with SPSS 21 software.Results: Most of the respondent were nurses who work in Covid ward (64.4%) and majority is an associate nurse (84.9%). The p value was 0.077 (p0.05) which indicate that there were not differences of family support between nurses who work in Covid and non-Covid wards.Conclusion: There were not differences of family support between nurses who work in Covid and non-Covid wards.